THE RELATION BETWEEN LAND OCCUPATION, DENSITY AND SPATIAL FRAGMENTATION (SPAIN 1956-2006) - Yraida Romano; Nicola Colaninno; Jorge Cerda; Josep Roca; Malcolm Burns (European Regional Science Association (ERSA), 2010)
The European political discourse has denounced the increase in land consumption in Spain, resulting from contemporary processes of urban development. The occupation of land deriving from demographic dynamics generates different patterns of urban growth, defining spatial structures with different degrees of fragmentation of urbanised areas. This study analyses the spatial relation of urban growth in Spain over the period 1956-2006 in three dimensions; land occupation, population density and the fragmentation of artificialised urban areas. The methodology consists of the construction of a number of specific indicators of land occupation (%), population density (net and administrative), and fragmentation (Shannon's evenness), in order to apply a relational statistical analysis (change over time and change between variables), as well as examine the likely future performance of these three indicators The results indicate that in general in the areas studied the decrease in the net density and the rates of expansion of artificialised land have been greater than the rate of population growth. However the spatial fragmentation has reduced over the period under review. Finally it needs to be highlighted that the descriptive analysis identified landscapes of special performance (outside the overall tendency), which cannot be detected under the integrated 'relational' focus. Although the results do not indicate the value of one method with respect to the other, it can be confirmed that that the integrated focus is more complete in its conception and its capacity to explain complex phenomenon, than the partial vision offered by the indicators.
Keywords: 330; land consumption; density; fragmentation; integrated analysis